Effects of Compudose® implants from birth to slaughter on carcass and meat traits of young bulls and steers - Hopkins, T.D.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Implanting young bulls with Compudose® three times from birth to slaughter resulted in performance similar to that of nonimplanted bulls, but decreased masculinity development. Implanted bulls tended to have higher marbling scores, more tender meat, more youthful carcasses, and lighter lean color than nonimplanted bulls. Although both implanted and nonimplanted bulls were more efficient and gained faster in the feedlot than implanted steers, the steers showed very little carcass masculinity and had finer-textured lean. Implanted steers had more youthful carcasses and lower Warner-Bratzler shear values than nonimplanted bulls. However, nonimplanted bulls grew faster, were more efficient, had larger ribeyes and lower yield grade numbers than implanted steers. For large-framed cattle, castration and implanting with Compudose® near birth result in the most desirable combination of performance, carcass, and meat quality traits.
Keywords: Beef; Compudose® implants; Carcass; Meat traits